Co-circulation of Four Human Coronaviruses (HCoVs) in Queensland Children with Acute Respiratory Tract Illnesses in 2004 - Theo P. Sloots; Ristan M. Greer; Michael D. Nissen; Peter K. McErlean; Nicholas T. O’Neil; Katherine E. Arden; David J. Speicher; Ian M. Mackay (Viruses, 2012)
Acute respiratory illnesses (ARIs) with unconfirmed infectious aetiologies peak at different times of the year. Molecular diagnostic assays reduce the number of unconfirmed ARIs compared to serology- or culture-based techniques. Screening of 888 inpatient and outpatient respiratory specimens spanning late autumn through to early spring, 2004, identified the presence of a human coronavirus (HCoV) on 74 occasions (8.3% of all specimens and 26.3% of all respiratory virus detections). Prevalence peaked in August (late winter in the southern hemisphere) when they were detected in 21.9% of specimens tested. HCoV-HKU1 and HCoV-OC43 comprised 82.4% of all HCoVs detected. Positive specimens were used to develop novel reverse transcriptase real-time PCRs (RT-rtPCRs) for HCoV detection. An objective clinical severity score was assigned to each positive HCoV patient. Severity scores were similar to those from a random selection of young children who were positive for respiratory syncytial virus at a different time but from the same specimen population. During the cooler months of 2004, sensitive and specific RT-rtPCRs identified the concurrent circulation of all four HCoVs, a quarter of which co-occurred with another virus and most of which were from children under the age of two years.